2009
DOI: 10.1103/physrevlett.102.228102
|View full text |Cite
|
Sign up to set email alerts
|

Model Lipid Membranes on a Tunable Polymer Cushion

Abstract: A hydrated, surface-tethered polymer network capable of fivefold change in thickness over a 25-37 degrees C temperature range has been demonstrated via neutron reflectivity and fluorescence microscopy to be a novel support for single lipid bilayers in a liquid environment. As the polymer swells from 170 to 900 A, it promotes both in- and out-of-plane fluctuations of the supported membrane. The cushioned bilayer proved to be very robust, remaining structurally intact for 16 days and many temperature cycles. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 15 publications
1
53
0
Order By: Relevance
“…number of compounds has been found suitable for this purpose, in particular polymers [17,22] and oligomers [23][24][25][26] of ethyleneoxide but also oligopeptides bearing thiol groups [27] and acrylates. [28][29][30][31][32][33][34] In a series of contributions we and others demonstrated that tailored poly(2-oxazoline) (POx) lipopolymers are a highly versatile system for the construction of PTMs. [35][36][37][38][39][40][41][42][43][44] POx-based PTMs have been successfully used to determine lateral mobility and functionality of reconstituted membrane proteins, [17,23,41,42,45] to modulate the interactions between substrate and membrane [46] but also the PTM structure.…”
Section: Introductionmentioning
confidence: 99%
“…number of compounds has been found suitable for this purpose, in particular polymers [17,22] and oligomers [23][24][25][26] of ethyleneoxide but also oligopeptides bearing thiol groups [27] and acrylates. [28][29][30][31][32][33][34] In a series of contributions we and others demonstrated that tailored poly(2-oxazoline) (POx) lipopolymers are a highly versatile system for the construction of PTMs. [35][36][37][38][39][40][41][42][43][44] POx-based PTMs have been successfully used to determine lateral mobility and functionality of reconstituted membrane proteins, [17,23,41,42,45] to modulate the interactions between substrate and membrane [46] but also the PTM structure.…”
Section: Introductionmentioning
confidence: 99%
“…Simple systems NR is frequently executed to evaluate film thickness, roughness, packing, and chemical composition, but can also reveal the response of a (multi-)layer to external stimuli such as UV light, 56 shear, 46,57,58 electric fields, [59][60][61] change in temperature, 38,62,63 hydration, 38,64,65 or pH.…”
Section: Resultsmentioning
confidence: 99%
“…2,30 Typically, NR measurements are performed on homogeneous model systems, such as phospholipid monolayers at the air-liquid interface, 31 pure and hybrid phospholipid bilayers on silicon and quartz substrates, [32][33][34][35] and supported phospholipid bilayers mimicking biological membranes. [36][37][38] For more information, we refer the interested reader to several recent reviews and publications. 3,30,[39][40][41][42] Small angle neutron scattering is also frequently employed to study living matter.…”
Section: Introductionmentioning
confidence: 99%
“…However, even in the 'unhydrated form' approximately 50% of the film volume is occupied by [25][26][27] The detailed preparation method of pNIPAM film is described elsewhere. [25][26][27] Briefly, the pNIPAM was spin coated onto a quartz substrate covered by a monolayer of 3-aminopropyl-triethoxysilane.…”
Section: Pnipaam Thin Film Under the Liquid Flow-shearmentioning
confidence: 99%